Effect of estradiol on in vitro maturation of immature oocytes in cyclophosphamide-induced premature ovarian failure in NMRI mice: An experimental study - Yasaman Sohani; Mahnaz Azarnia; Hadis Zeinali; Sajed Khaledi; Mehdi Mehdinezhad Roshan (International Journal of Reproductive BioMedicine)
Background: Premature ovarian failure (POF) is a condition characterized by the loss of ovarian function, leading to infertility.